Characterization of Kidney Stones type using Raman Spectrosco-py and Electron Microscopy - Sładek, Michał; Procek, Marcin; Drewniak, Sabina; Kałużyński, Piotr; Maciak, Erwin (Photonics Letters of Poland, 2025)
Raman spectroscopy (RS) is an excellent photonic measurement technique that can be extremely useful for characterizing kidney stones. Using RS, we can obtain precise information about the chemical composition and microstructure of the crystals that comprise kidney stones. Therefore, this non-invasive technique makes identifying different types of stones possible. Additionally, Raman spectroscopy supported by electron microscopy (SEM) imaging enables us to relate a given kind of crystal to its morphology. This paper presents the results of ex situ analysis of real samples of an unknown type of human kidney stone using RS and SEM techniques, which led to attempts to identify the stone. Full Text: PDF References P.J.S. Osther, Epidemiology of Kidney Stones in the European Union (Springer London, 2013). CrossRef G. Zeng, Z. Mai, S. Xia, Z. Wang, K. Zhang, L. Wang, Y. Long, J. Ma, Y. Li, S.P. Wan, W. Wu, Y. Liu, Z. Cui, Z. Zhao, J. Qin, T. Zeng, Y. Liu, X. Duan, X. Mai, Z. Yang, Z. Kong, T. Zhang, C. Cai, Y. Shao, Z. Yue, S. Li, J. Ding, S. Tang, Z. Ye, "Prevalence of kidney stones in China: an ultrasonography based cross-sectional study", BJU Int. 120(1), 109 (2017). CrossRef K. Christian, M. Johanna, A. Werner, B. Kathrin, G.M. Tesfay, R.H. Abbas A, W. Stefan, B. Andreas, N.F. Wilhelm, S. Florian, "Raman difference spectroscopy: a non-invasive method for identification of oral squamous cell carcinoma", Biomed Opt. Express 5(9), 3252 (2014). CrossRef C.A. Lieber, H.E. Nethercott, M.H. Kabeer, "Cancer field effects in normal tissues revealed by Raman spectroscopy", Biomed. Opt. Express 1(3), 975 (2010). CrossRef S. Feng, R. Chen, J. Lin, J. Pan, G. Chen, Y. Li, M. Cheng, Z. Huang, J. Chen, H. Zeng, "Nasopharyngeal cancer detection based on blood plasma surface-enhanced Raman spectroscopy and multivariate analysis", Biosens. Bioelectron. 25(11), 2414 (2010). CrossRef X. Cui, Z. Zhao, G. Zhang, S. Chen, Y. Zhao, J. Lu, "Analysis and classification of kidney stones based on Raman spectroscopy", Biomed. Opt. Express 9(9), 4175 (2018). CrossRef Y.-Ch. Hsu, Y.-H. Lin, L.-D. Shiau, "Effects of Various Inhibitors on the Nucleation of Calcium Oxalate in Synthetic Urine", Crystals 10, 333 (2020). CrossRef P. Chatterjee, A. Chakraborty, A. Mukherjee, "Phase composition and morphological characterization of human kidney stones using IR spectroscopy, scanning electron microscopy and X-ray Rietveld analysis", Spectrochimica Acta Part A: Molecular and Biomolecular Spectroscopy 200, 33 (2018). CrossRef W. Różański, Przegląd Urologiczny 6(58), 34 (2009). DirectLink C. Conti, L. Brambilla, C. Colombo, D. Dellasega, G. Diego Gatta, M. Realini, G. Zerbi, "Stability and transformation mechanism of weddellite nanocrystals studied by X-ray diffraction and infrared spectroscopy", Physical Chemistry Chemical Physics 43, 14560 (2010). CrossRef J. Duława, "Czynniki rozwoju kamicy nerkowej", Forum Nefrologiczne 3, 2, (2009). DirectLink J.W. Robinson, W.W. Roberts, A.J. Matzger, "Kidney stone growth through the lens of Raman mapping", Sci. Rep. 14, 10834 (2024). CrossRef E. Yakubovskaya, T. Zaliznyak, J. Martínez Martínez, et al., "Tear Down the Fluorescent Curtain: A New Fluorescence Suppression Method for Raman Microspectroscopic Analyses", Sci. Rep. 9, 15785 (2019). CrossRef